2021
DOI: 10.1140/epje/s10189-021-00140-8
|View full text |Cite
|
Sign up to set email alerts
|

Wetting between Cassie–Baxter and Wenzel regimes: a cellular model approach

Abstract: The cellular model with periodic boundary conditions was proposed for the study of liquid–solid interface properties of solid surfaces decorated by a regular pattern. The solid surface was represented by a mosaic of truncated pyramids of two different slopes of side walls equivalent to a surface covered with triangular grooves of different dihedral angles. On the basis of the computations performed for a single elementary cell, the components of the interfacial energies and the apparent contact angles have bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 30 publications
(46 reference statements)
0
4
0
Order By: Relevance
“…25,41 This can be explained by assuming that the addition of 30% PFOTES/TiO 2 NPs was not sufficient to create hydrophobic nano/microstructures on the surface, suggesting that the sample was in the intermediate region between the Wenzel and Cassie-Baxter states. [42][43][44] Thus, it was concluded that 40-60% PFOTES/TiO 2 NPs in the composite were optimal for producing a superhydrophobic surface in the Cassie-Baxter state. The composites containing 40, 50 and 60% PFOTES/TiO 2 NPs with an S a of ∼17 mm were selected as superhydrophobic surfaces.…”
Section: Resultsmentioning
confidence: 99%
“…25,41 This can be explained by assuming that the addition of 30% PFOTES/TiO 2 NPs was not sufficient to create hydrophobic nano/microstructures on the surface, suggesting that the sample was in the intermediate region between the Wenzel and Cassie-Baxter states. [42][43][44] Thus, it was concluded that 40-60% PFOTES/TiO 2 NPs in the composite were optimal for producing a superhydrophobic surface in the Cassie-Baxter state. The composites containing 40, 50 and 60% PFOTES/TiO 2 NPs with an S a of ∼17 mm were selected as superhydrophobic surfaces.…”
Section: Resultsmentioning
confidence: 99%
“…Then, these three interfacial tensions (solid-liquid, liquid-gas, and solid-gas interfacial tensions) must be balanced to the total surface free energy to describe the corresponding contact angle [39]. However, to explain the behavior of a droplet by the WCA on a rough surface, the protuberances of these surfaces must be considered as the main feature [34,40]. The roughness effect on the surfaces could be described by the fundamental states known as Wenzel State and Cassie-Baxter State to describe how a droplet of water interacts with a surface (Figure 3).…”
Section: Roughness Effect In Hysteresis Tilt Angle and Wettability In...mentioning
confidence: 99%
“…The presence of hysteresis between the curve of the textured surface and the straight flat one draws attention. The classic Cassie-Baxter equation can be used to describe its upper part, and the Wenzel equation to describe the lower part [9].…”
Section: Analysis Of Recent Researchmentioning
confidence: 99%